Early blood transcriptomic signature predicts patients' outcome after out-of-hospital cardiac arrest. (May 2019) - Tissier, Renaud; Hocini, Hakim; Tchitchek, Nicolas; Deye, Nicolas; Legriel, Stéphane; Pichon, Nicolas; Daubin, Cédric; Hermine, Olivier; Carli, Pierre; Vivien, Benoît; Tréluyer, Jean-Marc; Lefebvre, Cécile; et al.
Abstract: Background: Early prognostication is a major challenge after out-of-hospital cardiac arrest (OHCA). Aims: We hypothesized that a genome-wide analysis of blood gene expression could offer new prognostic tools and lines of research. Methods: Sixty-nine patients were enrolled from an ancillary study of the clinical trial NCT00999583 that tested the effect of erythropoietin (EPO) after OHCA. Blood samples were collected in comatose survivors of OHCA at hospital admission and 1 and 3 days after resuscitation. Gene expression profiles were analyzed (Illumina HumanHT-12 V4 BeadChip; >34, 000 genes). Patients were classified into two categories representing neurological favorable outcome (cerebral performance category [CPC] = 1-2) vs unfavorable outcome (CPC > 2) at Day 60 after OHCA. Differential and functional enrichment analyses were performed to compare transcriptomic profiles between these two categories. Results: Among the 69 enrolled patients, 33 and 36 patients were treated or not by EPO, respectively. Among them, 42% had a favorable neurological outcome in both groups. EPO did not affect the transcriptomic response at Day-0 and 1 after OHCA. In contrast, 76 transcripts differed at Day-0 between patients with unfavorable vs favorable neurological outcome. This signature persisted at Day-1 after OHCA. Functional enrichment analysis revealed a down-regulation of adaptive immunity with concomitant up-regulation of innate immunity and inflammation in patients with unfavorable vs favorable neurological outcome. The transcription of many genes of the HLA family was decreased in patients with unfavorable vs favorable neurological outcome. Concomitantly, neutrophil activation and inflammation were observed. Up-stream regulators analysis showed the implication of numerous factors involved in cell cycle and damages. A logistic regression including a set of genes allowed a reliable prediction of the clinical outcomes (specificity = 88%; Hit Rate = 83%). Conclusions: A transcriptomic signature involving a counterbalance between adaptive and innate immune responses is able to predict neurological outcome very early after hospital admission after OHCA. This deserves confirmation in a larger population.